Microfluidic purification of genomic DNA - Jiayi Wang; Jason E. Butler; Anthony J. C. Ladd (Proceedings of the National Academy of Sciences, 2025)
We describe a microfluidic device to extract DNA from a cell lysate, without the need for centrifuges, magnetic beads, or gels. Instead, separation is driven by transverse migration of DNA, which occurs when a polyelectrolyte solution flowing through a microfluidic channel is subjected to an electric field. The coupling of the weak shearing with the axial electric field is highly selective for long, flexible, charged molecules, of which DNA is the sole example in a typical cell lysate. As a result of migration to the walls, DNA is held near the channel inlet by electrophoresis (there is no flow near the channel walls), while the remaining components are eluted by the much larger (at least 10-fold) convective flow. We have demonstrated the feasibility of the device by recovering up to 40 ng of purified DNA in less than 30 min from 10 μ L of Escherichia coli lysate. Gel electrophoresis indicates minimal additional fragmentation during purification, up to the maximum length recorded by the gel (60 kbp). Electropherograms were also obtained for purified mammalian DNA, using a Femto Pulse system (fragment lengths up to 165 kbp). Extracted samples show strong amplification by PCR, while the original lysate does not. Mixtures of λ -DNA and BSA were used to determine the extent of the separation of DNA from a physiological concentration of proteins (30 mg/mL). The protein concentration in the extract (0.3 to 0.5 ng/µL) was reduced by five orders of magnitude from the initial mixture.